2017
DOI: 10.1002/brb3.646
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant within STS previously associated with inattention in boys with attention deficit hyperactivity disorder is associated with enhanced cognition in healthy adult males

Abstract: IntroductionThe enzyme steroid sulfatase (STS) converts sulfated steroids to their non‐sulfated forms. Deficiency for this enzyme is associated with inattention but preserved response control. The polymorphism rs17268988 within the X‐linked STS gene is associated with inattentive, but not other, symptoms in boys with attention deficit hyperactivity disorder (ADHD).MethodsWe initially tested whether rs17268988 genotype was associated with attention, response control, and underlying aspects of cognition, using q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…In conclusion, we could not confirm the supposed connection between response inhibition, ADHD (Crosbie et al, ) and CHRNA5 in our sample, however, an interesting influence of CHRNA5 genotype, sex and ADHD symptoms on reaction time was found. This does not only replicate, but extend previous findings (Humby et al, ; Schneider et al, ) as sex, genotype and ADHD symptom interactions have rarely been reported before. Although explorative, these results might inspire future research and the development of gender‐specific ADHD‐medication.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In conclusion, we could not confirm the supposed connection between response inhibition, ADHD (Crosbie et al, ) and CHRNA5 in our sample, however, an interesting influence of CHRNA5 genotype, sex and ADHD symptoms on reaction time was found. This does not only replicate, but extend previous findings (Humby et al, ; Schneider et al, ) as sex, genotype and ADHD symptom interactions have rarely been reported before. Although explorative, these results might inspire future research and the development of gender‐specific ADHD‐medication.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies showed that subjects homozygous for the minor S allele of rs3841324 showed a 2.9‐fold increase in CHRNA5 mRNA levels in frontal cortex compared with major allele homozygotes (Wang, Grucza, et al, ). A similar, and to our knowledge only other interaction effect of a genetic variant and ADHD on cognitive performance, has recently been demonstrated by Humby and colleagues (). In their study, the G‐allele of rs17268988 of the X‐linked steroid‐sulfatase gene ( STS ) was associated with enhanced cognitive performance in healthy adult men without ADHD and with lower attention symptoms in boys with ADHD.…”
Section: Discussionsupporting
confidence: 80%
“…Volumetric analysis of subcortical regions suggests that the smaller size of basal ganglia sub‐regions important in maintaining focus and regulating impulse control in deletion carriers may be relevant. 9 Numerous lines of evidence implicate STS specifically in ADHD‐related endophenotypes: (a) individuals with gene‐specific point mutations meet diagnostic criteria, 33 (b) the gene is highly‐expressed in the developing basal ganglia, 56 (c) within‐gene variation is associated with (in)attentive (but not impulsivity) symptoms in boys with ADHD 56 and healthy men, 57 (d) independent mouse models lacking STS indicate impairments in attention, 43 , 58 reduced motor impulsivity, 41 and altered basal ganglia serotonergic neurochemistry, 59 and (e) circulating DHEA levels inversely correlate with symptom severity 60 and are sensitive to pharmacotherapy. 61 The neurobehavioural features and executive function deficits seen in some individuals with XLI could be exacerbated by poor sleep quality (due to night‐time discomfort/itching, stress, or aberrant temperature regulation 62 , 63 ) and, if so, might be ameliorated through sleep‐based interventions.…”
Section: Newly‐identified Medical Comorbiditiesmentioning
confidence: 99%
“…A study examining 384 patients with ADHD identified two SNPs in the STS gene significantly associated with this condition (Brookes et al 2008). Indeed, the polymorphism rs17268988 within the STS gene is associated with inattentive behavior in males with ADHD (Humby et al 2017). More recently, XLI patients have been shown to be at a significantly increased risk of developmental conditions and psychiatric illness (Chatterjee et al 2016).…”
Section: Steroid Sulfation Pathways the Brain And Behaviormentioning
confidence: 99%